Analisis penerapan pajak atas penggunaan dana desa di Desa Wiau Lapi Barat Kecamatan Tareran Kabupaten Minahasa Selatan - Kumaat, Swinglie K.; Budiarso, Novi Swandari; Weku, Priscillia (Riset Akuntansi dan Portofolio Investasi, 2024)
This study aims to analyze the implementation of taxes on the use of village funds in Wiau Lapi Barat Village, Tareran District, South Minahasa Regency. Village funds are one of the sources of income for village governments originating from the State Revenue and Expenditure Budget (APBN). In accordance with the laws and regulations, the use of village funds must be subject to taxes. The research method used is a qualitative descriptive method. Data were collected through interviews, observation, and documentation studies. The informants in this study consisted of village officials. The results showed that the implementation of taxes on the use of village funds in Wiau Lapi Barat Village has not fully complied with the applicable regulations. There are still several obstacles, including the lack of understanding of village officials and the community regarding the obligation to deposit and report taxes, as well as the limited resources in village tax administration. In addition, there is potential for tax revenue that has not been optimally explored. The conclusion of this study is the need to increase the understanding and capacity of village officials as well as synergy between the village government, local government, and related agencies in the implementation of taxes on the use of village funds. This is expected to improve tax compliance and village tax revenue, thereby supporting village development and community welfare.